CONTRIBUTION ANALYSIS OF INDIRECT RESERVATION SOURCES TO THE ROOM OCCUPANCY AT FOUR POINTS BY SHERATON BALI, KUTA - Wayan Aries Dana Surya; Ni Nyoman Sri Astuti; I Gusti Agung Bagus Mataram (Politeknik Negeri Bali, 2019)
This research was conducted to analyze the contribution of indirect reservation sources at Four Points by Sheraton Bali, Kuta. The purpose of this research are to find out the source of reservation, how the indirect reservation sources influence room occupancy, and how the contribution of indirect reservation sources (wholesaler and online travel agent) is at Four Points by Sheraton Bali, Kuta. The data of this research are the reservation contribution and room occupancy for 36 months within period of 2016-2018. The data analysis technique of this research is quantitative analysis to find the effect of indirect reservation sources on room occupancy, also qualitative analysis in the form of quantitative descriptive to interpret numerical data and qualitative descriptive to interpret word information data. This study resulting that the sources of indirect reservation are wholesaler and online travel agent. The results shows that wholesaler has a moderate influence (0,467) and online travel agent has a strong influence (0,685) towards room occupancy partially, however they have a very strong influence (0,849) simultaneously. This study also resulting that indirect reservations (wholesalers and online travel agent) are the major contributors toward room occupancy at Four Points by Sheraton Bali, Kuta with an average of 3,035 nights in 2016, 2,668 nights in 2017, and 3,015 nights in 2018.